PERANCANGAN PLTS GROUND MOUNTED DI AREA TERBUKA PUSAT PEMERINTAHAN KABUPATEN BADUNG - Yosep, T.I.; Setiawan, I N.; Sukerayasa, I W.; Giriantari, I. A. D.; Ariastina, W. G.; Kumara, I N. S. (Jurnal SPEKTRUM, 2025)
According to the National Energy General Plan (RUEN), Bali Province has the potential for electricity generation by utilizing renewable energy, namely solar energy of 1.254 MW; however until 2020, the installed PV system in Bali Province is 3,71 MWp. To support the achievement of this target, the Bali provincial government through the Governor's regulation No. 45/2019 encourages the utilization of rooftop PV systems. This research aims to design a ground mounted PV system by utilizing vacant land in Badung Government Center area. The design of the PV system was simulated using Helioscope software, using 264 Trina Solar 575 Wp modules, three Growatt MID 50KTL3-X2 inverters. The simulation r results show that the ground-mounted solar power plant is capable of producing an annual energy production of 252,9 MWh.